Colony personality and plant health in the Azteca-Cecropia mutualism. (5th December 2017) - Marting, Peter R; Wcislo, William T; Pratt, Stephen C
Abstract : Deep in the rainforest, Azteca ant colonies gallantly defend their nourishing Cecropia home-trees from leaf-eaters and choking vines. It turns out that some colonies defend more gallantly than others in a suite of behavioral traits measured in the field, revealing that colonies themselves have personalities. Trees that have more active, aggressive colonies have less leaf damage, suggesting that colony personality plays an important role in this intimate mutualism. Abstract: For interspecific mutualisms, the behavior of one partner can influence the fitness of the other, especially in the case of symbiotic mutualisms where partners live in close physical association for much of their lives. Behavioral effects on fitness may be particularly important if either species in these long-term relationships displays personality. We conducted a field study on collective personality in Azteca constructor colonies that live in Cecropia trees, one of the most successful and prominent mutualisms of the neotropics. These pioneer plants provide hollow internodes for nesting and nutrient-rich food bodies; in return, the ants provide protection from herbivores and encroaching vines. We tested the consistency and correlation of 5 colony-level behavioral traits, censused colonies, and measured the amount of leaf damage for each plant. Four of five traits were both consistent within colonies and correlated among colonies. This reveals a behavioral syndrome along a docile-aggressive axis, with higher-scoring colonies showing greater activity, aggression, and responsiveness. Scores varied substantially between colonies and were independent of colony size and age. Host plants of more active, aggressive colonies had less leaf damage, suggesting a link between a colony's personality and effective defense of its host, though the directionality of this link remains uncertain. Our field study shows that colony personality is an ecologically relevant phenomenon and sheds light on the importance of behavioral differences within mutualism dynamics.